Cellular angiofibroma of the female pelvic cavity: a case report - Li Chen; Gumuyang Zhang; Hao Sun (BMC Urology)
Abstract Background Cellular angiofibroma is a rare benign mesenchymal tumor that mostly occurs in the genital area. Its occurrence outside this region, particularly in the pelvis, is extremely rare. To our knowledge, this study reports the first case of cellular angiofibroma occurring in the pelvic cavity, except for one case reported in the retroperitoneum. Case presentation A 25-year-old female patient with chronic, intermittent, dull pain in the lower abdomen that lasted for several months was referred to our clinic. Imaging studies revealed a tumor in the pelvic cavity anterior to the bladder. The radiographic characteristics of this tumor indicated a hypervascular nature, suggesting the possibility of a pheochromocytoma or a neuroendocrine tumor. The patient underwent surgical excision of the lesion. To date, no recurrence has been observed four months after excision. Conclusions Cellular angiofibroma, although rare in the pelvic cavity, should be considered in the differential diagnosis of hypervascular pelvic space-occupying lesions. Immunohistochemical staining can help confirm the diagnosis of this condition. Treatment is generally straightforward, involving local excision of the tumor followed by postoperative monitoring.